Prevention of Credit Card Fraudulence in Point-of-Sale Terminus (International Journal of Engineering and Computer Science, 2017)
The credit card fraudulence has become more vulnerable threat in recent days. The period between the credit card theft and blocking of it is sufficient for intruder to get away with all amount in it by swiping in POS (Point-Of-Sale) Terminus and stealing the entire amount in it. It can be prevented by taking the cumulative average of first 'n'(eg 10) transactions that has done by the user in that credit card through POS and when the next transaction has been done, if the Standard Deviation of amount usage is more than average of first 'n' transactions, then the banks should enable PIN(Personal Identification Number) for that particular transaction and if the PIN entered is wrong, the card will be blocked and the user should go to bank in person and reveal his identity and activate the card again